From Monobank to Commercial Banking Financial Sector Reforms in Vietnam - Kovsted, Jens; Rand, John; Tarp, Finn (ISEAS Publishing, 2005)
This study analyses the difficulties and problems encountered in transforming the Vietnamese financial sector from one that is subordinate to government objectives and goals to an autonomous sector guided by market forces and competitive pressures. Here, the history of financial sector liberalization is traced and close attention paid to the activities and autonomy of the State Bank of Vietnam, the institution responsible for the supervision and regulation of the financial sector in Vietnam. Overall, the authors argue that ensuring a timely, fair and transparent supervision and regulation of the financial sector is of central importance to financial sector development and stability. Liberalizing financial markets is not solely a question of limiting and/or restricting government influence but may in fact involve the opposite, the influence and power of supervisory and regulatory institutions in many cases needing to be strengthened
Description based on online resource; title from PDF title page (publisher's Web site, viewed 22. Jun 2018)